MENINGKATKAN HASIL BELAJAR SISWA SD NEGERI CIMANGGU KECIL DALAM MEMAHAMI PROSEDUR AKTIVITAS DAYA TAHAN JANTUNG DAN PARU UNTUK PENGEMBANGAN KEBUGARAN JASMANI MELALUI PERMAINAN LOMPAT TALI - Hasan Basri (Universitas Pakuan, 2021)
IMPROVING LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS IN UNDERSTANDING HEART AND LUNG ENDURANCE ACTIVITIES PROCEDURES FOR THE DEVELOPMENT OF PHYSICAL FITNESS THROUGH JUMPING ROPE GAMESThis research departs from the low quality of mastery of techniques in the subjects of Physical Education, Sports and Health in understanding the procedures for cardiovascular endurance activities for the development of physical fitness that can have an influence on student activities and learning outcomes. Teachers need to consider effective and fun learning models so that they can improve student learning outcomes. One of the learning approaches that was tried through this research was the application of the Jump Rope Game. The study was conducted in Class VA of SDN Cimanggu Kecil, Bogor City, Semester 1 of the 2019/2020 Academic Year and aimed: (1) To find out the improvement in student learning outcomes about Understanding the procedures for heart and lung endurance training activities for the development of physical fitness by using the Jump Rope Game. (2) To describe the process of improving student learning outcomes about understanding the procedures for heart and lung endurance training activities for the development of physical fitness using the Jump Rope Game for students. (3) To measure how much the increase in student learning outcomes regarding understanding the procedure for heart and lung endurance training activities for the development of physical fitness through the Jump Rope Game for students. The results of this study indicate that by using the Jump Rope Game on Understanding the procedure for cardio respiratory endurance training activities for the development of physical fitness in students in learning using the Jump Rope Game, the average student learning outcome increases to 73.85 in the Cycle. I and 91.15 in Cycle II. From the description above, the researcher concludes that the Jump Rope Game applied by the teacher can improve student learning outcomes, therefore the researcher suggests that the use of the Jump Rope Game be socialized and used as an alternative in learning Physical Education, Sports and Health in Schools within the Education Office. Bogor cityÂ